Immune-Related Prognostic Model in Colon Cancer: A Gene Expression-Based Study - Yang, Haojie; Jin, Wei; Liu, Hua; Gan, Dan; Cui, Can; Han, Changpeng; Wang, Zhenyi (Frontiers in Genetics, 2020)
Objective: The aim of this study was to develop an immune-related model associated with colon cancer prognosis based on the gene expression profiles of immune-related genes and TCGA clinical data of colon cancer. Methods: The colon cancer gene and miRNA expression profiles data as well as clinical phenotype data were downloaded, followed by differential expression analysis of immune genes and miRNAs. Then the interaction networks of immune gene and miRNA-immune gene were constructed. Immune cell components were analyzed, and the diagnostic model and prognostic model of colon cancer were constructed based on immune characteristics. Finally nomogram visualized prognostic model was obtained. Results: Total 265 differentially expressed immune genes, and 268 differentially expressed miRNAs were identified. Endothelial cells, CD4+T cells, and CD8+T cells accounted for a relatively large proportion. B cells infiltration ratio, TRIB3, CHGA, CASP7, multiple LGALS family genes such as LGALS4 were important features in diagnostic prediction model. Additionally, 19 factors such as CD4+T cells, LEP, NOX4, IL17A, HSPD1 and CHGA had significant influence on prognostic model. In the nomogram visualized prognostic model, the C-index of the combined model was the highest. Pathologic M had significant statistical test result. Conclusion: Our analysis constructed an immune-related prognostic model of colon cancer. B cells infiltration ratio, CD4+T cells, as well as genes of TRIB3, CHGA, CASP7, LGALS4, LEP, NOX4, IL17A and HSPD1 may have important associations with clinical outcome of colon cancer.